2009
DOI: 10.1213/ane.0b013e318193873e
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine Injection into the Rat Dorsal Root Ganglion Causes Neuroinflammation

Abstract: BACKGROUND Injury of a spinal nerve or dorsal root ganglion (DRG) during selective spinal nerve blocks is a potentially serious complication that has not been adequately investigated. Our hypothesis was that local anesthetic injection into these structures may result in an inflammatory response and hyperalgesia. METHODS We evaluated inflammatory and behavioral responses after injection of 4 μL lidocaine or saline into the L5 spinal nerve or DRG of rats after partial laminectomy. Behavioral testing was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 26 publications
(27 reference statements)
1
23
0
Order By: Relevance
“…In the experimental setting it has been reported that topical application of local anesthetic to the DRG induces mechanical hyperalgesia in the rat,29 but possible morphological changes in the DRG have not been studied. We have found that the injection of lidocaine into a DRG induced pain-related behavior and a marked inflammatory response in the DRG 37. It is important that we also identified an inflammatory response in saline-injected rats, but this was not accompanied with marked hyperalgesia, perhaps because this inflammatory response was significantly lower than after the lidocaine injection suggesting that DRG injection can be a secure procedure 37…”
Section: Is Drg Injection Harmful?mentioning
confidence: 72%
See 1 more Smart Citation
“…In the experimental setting it has been reported that topical application of local anesthetic to the DRG induces mechanical hyperalgesia in the rat,29 but possible morphological changes in the DRG have not been studied. We have found that the injection of lidocaine into a DRG induced pain-related behavior and a marked inflammatory response in the DRG 37. It is important that we also identified an inflammatory response in saline-injected rats, but this was not accompanied with marked hyperalgesia, perhaps because this inflammatory response was significantly lower than after the lidocaine injection suggesting that DRG injection can be a secure procedure 37…”
Section: Is Drg Injection Harmful?mentioning
confidence: 72%
“…Our group evaluated the neuroinflammatory response following a lidocaine or saline injection into the DRG or the adjacent spinal nerve 37. We hypothesized that an inflammatory response may follow local anesthetic injection into the DRG and produce hyperalgesia.…”
Section: Is Drg Injection Harmful?mentioning
confidence: 99%
“…We have also found that injection per se (e.g. saline) into spinal nerve or DRG does not cause neuroinflammation (Puljak et al, in press). Thus, this approach using direct exposure of the DRG offers the greatest accuracy and produces minimal unintended effects.…”
Section: Discussionmentioning
confidence: 78%
“…Quantification of transgene expression in neurons or SGCs was determined as reported previously (Puljak, Kojundzic, Hogan, & Sapunar, ; Yu et al, ). Immunostaining of Tubb3 (a pan‐neuronal marker) and GFAP or GS (SGC markers) was used to distinguish neurons and SGCs, respectively.…”
Section: Methodsmentioning
confidence: 99%